Three Perspectives on the Experience of Support for Family Caregivers in First Nations Communities - Amber Ward; Laurie Buffalo; Colleen McDonald; Tanya L’Heureux; Lesley Charles; Cheryl Pollard; Peter G Tian; Sharon Anderson; Jasneet Parmar (Diseases, 2023)
There is a dearth of research on how family caregivers are supported in First Nations. We interviewed family caregivers, health and community providers, and leaders in two Alberta First Nations Communities about their experiences of care and support for the family caregivers in their communities. We employed a qualitative, collaborative participatory action research methodology. We drew on Etuaptmumk, the Mi’kmaw understanding of being in the world is the gift of multiple perspectives. Participants in this research included family caregivers (n = 6), health and community providers (n = 14), and healthcare and community leaders (n = 6). The overarching caregiving theme is the “Hierarchy of challenge”. Six themes capture the challenges faced by family caregivers: (one) “Caregiving is a demanding job”: yet “No one in a sense is taking care of them”; (two) difficult navigation: “I am unable to access that”; (three) delayed assessments and treatment “And I don’t know how they’re being missed”; (four) disconnected health records: “It’s kind of on you to follow up”; (five) racism, “It’s treated differently”; and, (six) social determinants of health, “A lot of these factors have been developing for the longest time”. This study provides evidence that family caregivers’ need to care for and to maintain their own wellbeing is not top of mind in policy or programs in these First Nations communities. As we advocate for support for Canadian family caregivers, we need to ensure that Indigenous family caregivers are also recognized in policy and programs.